Pattern Formation in a Reaction-Diffusion Predator-Prey Model with Weak Allee Effect and Delay - Hua Liu; Yong Ye; Yumei Wei; Weiyuan Ma; Ming Ma; Kai Zhang (Complexity)
In this paper, we establish a reaction-diffusion predator-prey model with weak Allee effect and delay and analyze the conditions of Turing instability. The effects of Allee effect and delay on pattern formation are discussed by numerical simulation. The results show that pattern formations change with the addition of weak Allee effect and delay. More specifically, as Allee effect constant and delay increases, coexistence of spotted and stripe patterns, stripe patterns, and mixture patterns emerge successively. From an ecological point of view, we find that Allee effect and delay play an important role in spatial invasion of populations.